1993
DOI: 10.1164/ajrccm/147.5.1112
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Exercise-induced Airway Narrowing in Schoolchildren from a Mediterranean Town

Abstract: A cross-sectional study was carried out on a random sample of 2,216 schoolchildren 9 to 14 yr of age to determine the prevalence of exercise-induced airway narrowing (EIAN) in a Mediterranean town (Mataró). A complementary case-control study measured the association between EIAN and respiratory symptoms. A free-running test was performed during school time. Peak expiratory flow rate (PEFR) was measured at rest and at 2, 5, 10, and 15 min after exercise. A total of 136 of 2,056 satisfactory runs showed a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 17 publications
0
28
1
2
Order By: Relevance
“…The exclusion of these 25 has a small influence on the prevalence of bronchial responsiveness (11.4 versus 10.5%). Since reduction in PEFR due to fatigue was not studied by BARDAGÍ et al [15], it is not known whether differences in the prevalence of bronchial responsiveness after running between the present study and that of BARDAGÍ et al [15] may be attributed to the previously mentioned fatigue effect. In Zimbabwean children, the prevalence of exerciseinduced bronchoconstriction varied from 5.8% in an urban area with high living standards to 0.1% in a rural district [26].…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…The exclusion of these 25 has a small influence on the prevalence of bronchial responsiveness (11.4 versus 10.5%). Since reduction in PEFR due to fatigue was not studied by BARDAGÍ et al [15], it is not known whether differences in the prevalence of bronchial responsiveness after running between the present study and that of BARDAGÍ et al [15] may be attributed to the previously mentioned fatigue effect. In Zimbabwean children, the prevalence of exerciseinduced bronchoconstriction varied from 5.8% in an urban area with high living standards to 0.1% in a rural district [26].…”
Section: Discussionmentioning
confidence: 50%
“…In Zimbabwean children, the prevalence of exerciseinduced bronchoconstriction varied from 5.8% in an urban area with high living standards to 0.1% in a rural district [26]. Different prevalence rates in populations with a similar genetic background are illustrated by studies in Barcelona and Mataró [15]. In Zimbabwe, KEELEY et al [26] have also shown large differences in prevalence of reversible airway obstruction between populations living in close geographical proximities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations